Analisis Pengaruh Harga dan Kualitas Produk terhadap Loyalitas Pelanggan dengan Kepuasan Pelanggan sebagai Variabel Mediasi pada Anteiku Kopi - Maya Trinariswari; Aziz Rizky Pratama; Anton Wibowo; Marjam Desma Rahadhini (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the effect of price and product quality on customer loyalty by considering the role of customer satisfaction as a mediating variable at Anteiku Kopi. The approach used is quantitative with purposive sampling method, involving 31 respondents who are active customers aged at least 17 years. Data collection was carried out through a questionnaire, then analyzed using SPSS software with a number of tests such as validity, reliability, linear regression, and mediation analysis. The research findings show that price and product quality have a positive and significant effect on customer satisfaction. However, satisfaction did not show a significant effect on customer loyalty, nor was it able to mediate the relationship between price and product quality on loyalty. Thus, Anteiku Kopi's customer loyalty is more influenced by other factors outside the product, such as visiting experience, emotional attachment to the brand, and loyalty programs offered